Stres, Motivasi Berprestasi, Bersyukur, dan Perceived Social Support: Analisis Optimisme pada Mahasiswa Penerima Beasiswa Bidikmisi - Musabiq, Sugiarti A; Sari, Adilla; Dewi, Hervi Utami Kusuma; Erdiaputri, Widya Aktivana; Assyahidah, Lu’lu Nurrahiimah (Mediapsi, 2018)
This study aimed to investigae the relationship between optimism with stress, gratitude, achievement motivation, and perceived social support on students of Bidikmisi Scholarship, an educational funding for prospective students who could not afford higher education costs yet have excellent academic potential to study at universities on top-tier undergraduate programs for the specified time period. This study used quantitative approach with correlational design. A total of 300 students from four different classes at University of Indonesia participated in this study. Of these, only 253 participant data (70 men and 183 women) could be analyzed. Data were collected by asking participants to complete series of questionnaires consisting of Life Orientation Test-Revised (LOTR) for optimism, Gratitude Questionaire-Six Items (GQ-6) for gratitude, Achievement Motives Scale-Revised (AMS-R) for achievement motivation, Perceived Stress Scale (PSS) for stress, and Social Provisions Scale (SPS) for social support. The results showed a significant relationship between optimism and stress (r=-0.158; p<0.05); optimism and achievement motivation (r=0.15; p<0.05); optimism and gratitude (r=0.267; p<0.05); and optimism and perceived social support (r=0.351; p<0.05). The result reveals that the higher the level of optimism that Bidikmisi Scholarship students have, the higher their gratitude, achievement motivation, and perceived social support become, and the lower the level of their stress will be.Penelitian ini dilakukan untuk menunjukkan hubungan antara optimisme dengan stres, rasa syukur, motivasi berprestasi, dan persepsi dukungan sosial pada mahasiswa penerima Beasiswa Bidikmisi. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian korelasional. Sebanyak 300 mahasiswa dari empat kelas di Universitas Indonesia berpartisipasi dalam penelitian ini. Dari 300 data, hanya 253 data peserta (70 pria dan 183 wanita) yang bisa diproses. Penelitian dilakukan dengan meminta peserta mengisi kuesioner yang terdiri dari Life Orientation Test-Revised (LOTR) untuk optimisme, Gratitude Questionaire-Six Items (GQ-6) untuk rasa syukur, Achievement Motives Scale-Revised (AMS-R) untuk motivasi berprestasi, Perceived Stress Scale (PSS) untuk stres, dan Social Provisions Scale (SPS) untuk dukungan sosial. Hasil penelitian menunjukkan hubungan yang signifikan antara optimisme dan stres (r=-0.158; p<0.05); optimisme dan motivasi berprestasi (r=0.15; p<0.05); optimisme dan rasa syukur (r=0.267; p<0.05); dan optimisme dan dukungan sosial yang dirasakan (r=0.351; p<0.05). Hal ini bermakna bahwa semakin tinggi tingkat optimisme mahasiswa, maka semakin tinggi pula rasa syukur, motivasi berprestasi, dan dukungan sosial yang dirasakan, serta semakin rendah tingkat stresnya.